2013
DOI: 10.4103/2141-9248.113654
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular fractures at veer Chandra Singh Garhwali Government Medical Science and Research Institute, Garhwal region, Uttarakhand, India: A retrospective study

Abstract: Background:Mandibular fractures constitute a substantial proportion of cases of maxillofacial trauma. Demographic data related to mandibular fractures are difficult to evaluate because of many variables associated with the studies. The information is as diverse as the countries and the people who inhabit them.Aim:This is a retrospective study designed to determine the site distribution, associated fracture and causes of mandibular fractures in patients presenting to the trauma centre of Veer Chandra Singh Garh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…The incidence of mandibular fracture in our study increased with increasing age from 0 to 30 years, and then relatively decreased from 31 years of age. This finding correlates with the finding by Mittal et al 9 and Natu et al 10 Lesser occurrence of fracture in 0 to 10 year group is mainly attributed to good parental care prevents them from serious injuries and the elastic nature of bone makes them less prone to fracture. 10 The incidence of mandible fractures is increased in adulthood due to more active participation in vehicle driving, interpersonal violence, contact sports, alcohol abuse, social and cultural activities.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence of mandibular fracture in our study increased with increasing age from 0 to 30 years, and then relatively decreased from 31 years of age. This finding correlates with the finding by Mittal et al 9 and Natu et al 10 Lesser occurrence of fracture in 0 to 10 year group is mainly attributed to good parental care prevents them from serious injuries and the elastic nature of bone makes them less prone to fracture. 10 The incidence of mandible fractures is increased in adulthood due to more active participation in vehicle driving, interpersonal violence, contact sports, alcohol abuse, social and cultural activities.…”
Section: Discussionsupporting
confidence: 82%
“…This is also the most common cause of mandibular fracture in the studies of other countries [1,6,9,[20][21][22][23][24]. Intentional injury and falls were the second common causes of mandibular fracture in the present study; in contrast to other studies which had shown falls [10,25] or intentional injury/violence [8,11,16,17] as the most common. The difference in the main cause of injury is largely dependent on the cities where studied were conducted, as well as, the population.…”
Section: Discussioncontrasting
confidence: 54%
“…Also, Gassner et al reported maxillary fractures to be the most frequently diagnosed in their study [ 27 ]. Mandibular fractures are believed to occur frequently because of its prominence [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%